MULTIVARIATE TIME SERIES MODELING OF THE DOLLAR-TO-NAIRA EXCHANGE RATES ON SOME SELECTED ECONOMIC VARIABLES - Ikegwu , Emmanuel Mmaduabuchi; Karokatose , Gbenga Ben; Obidiegwu , Samuel Okeke; Udo, Dan Saviour (Economics and Statistics Research Journal (ESRJ), 2025)
This study formulated a multivariate time series model for the monthly USD-to-Naira exchange rate using the time-series VECM approach with stationarity, co-integration, and Granger causality tests. The economic variables used for this study include inflation rate, money supply, and crude oil price, all of which were obtained from the official CBN website from January 2002 to August 2023. The collected data were analysed using VECM after testing for stationarity and confirming the existence of co-integration in the economic variable using E-Views 9.0. The results showed that VECM (1, 1) was the most suitable model for forecasting the dollar-to-naira exchange rate in Nigeria because there was at most one co-integrating vector in the model. The formulation of the VECM model led to the successful comparison of the Naira-USD exchange rate with the other models. Therefore, the study concluded that the vector error correction model (1, 1) was the appropriate model and made recommendations to policymakers to continue monitoring trends in the dollar-to-naira exchange rate, inflation rate, crude oil price, and money supply to implement and sustain policies aimed at maintaining macroeconomic stability.